2011
DOI: 10.4314/wajm.v29i6.68298
|View full text |Cite
|
Sign up to set email alerts
|

Malocclusion and its Impact on Quality of Life of School Children in Nigeria

Abstract: dentaire et son impact sur la qualité de vie des enfants scolarisés au Nigéria

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
17
3
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 15 publications
5
17
3
6
Order By: Relevance
“…The social disability domain of the OHIP-14 detected that children who felt a need for orthodontic treatment were more irritable than those who did not and this agrees with a previous study of urban children where the psychosocial domain was most noted to impact on quality of life of the children as far as self-perceived orthodontic need was concerned 28 . This further emphasizes the social impact of malocclusion on OHRQoL of individuals.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The social disability domain of the OHIP-14 detected that children who felt a need for orthodontic treatment were more irritable than those who did not and this agrees with a previous study of urban children where the psychosocial domain was most noted to impact on quality of life of the children as far as self-perceived orthodontic need was concerned 28 . This further emphasizes the social impact of malocclusion on OHRQoL of individuals.…”
Section: Discussionsupporting
confidence: 89%
“…This is similar to finding in previous studies where higher impacts were observed when Oral Health Impact Profile (OHIP-14) and its association with dental treatment needs of adolescents in a rural Nigerian community self-perceived oral health was poor 26,27 . More participants in this rural community based study reported an impact of their general dental wellbeing on their quality of life than in a previous study among urban Nigerian children 28 . This is probably a reflection of the lower oral health utilization among rural dwellers in this environment with attendant higher disease burden 10,29 .…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…However, the negative psychological impact of having a malocclusion can be a serious threat for the very quality of life a person should cherish (3)(4)(5). The literature is explicit with respect to the reports on the psychological issues faced by people with malocclusion (1)(2)(3)(4)(5)(6)(7)(8). Besides the psychological issues, malocclusion can be the cause of abnormal oropharyngeal functions (6).…”
Section: Introductionmentioning
confidence: 99%
“…Malocclusion per se is not a life-threatening condition (1,2). However, the negative psychological impact of having a malocclusion can be a serious threat for the very quality of life a person should cherish (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%